2015
DOI: 10.7326/m15-0469
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Combined Diet and Physical Activity Promotion Programs to Prevent Type 2 Diabetes Among Persons at Increased Risk: A Systematic Review for the Community Preventive Services Task Force

Abstract: Background Diabetes is a highly prevalent and costly disease. Studies indicate that combined diet and physical activity promotion programs can prevent type 2 diabetes among persons at increased risk. Purpose To systematically evaluate the evidence on cost, cost-effectiveness, and cost-benefit estimates of diet and physical activity promotion programs. Data Sources Cochrane Library, EMBASE, MEDLINE, PsycINFO, Sociological Abstracts, Web of Science, EconLit, and CINAHL through 7 April 2015. Study Selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 44 publications
4
109
1
5
Order By: Relevance
“…Our results are consistent with those of previous studies that found intensive lifestyle interventions aimed at reducing the incidence of type 2 diabetes among people with prediabetes to be cost effective, with a median cost of approximately $14,000/QALY gained (15). Our risk group analysis was also consistent with a previous study (30) of diabetes prevention interventions, in which those with higher levels of fasting plasma glucose or A1C had more favorable CE ratios than those at the lower end of the prediabetes spectrum.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are consistent with those of previous studies that found intensive lifestyle interventions aimed at reducing the incidence of type 2 diabetes among people with prediabetes to be cost effective, with a median cost of approximately $14,000/QALY gained (15). Our risk group analysis was also consistent with a previous study (30) of diabetes prevention interventions, in which those with higher levels of fasting plasma glucose or A1C had more favorable CE ratios than those at the lower end of the prediabetes spectrum.…”
Section: Discussionsupporting
confidence: 82%
“…For cost, we examined two scenarios: implementing the recommended intervention only in a group-based setting; and adding the cost of screening to identify those eligible for intervention. Group-based interventions generally have lower costs and results that are comparable to those of individual-based interventions (15). In the screening test scenario, we assumed a medical visit with a lipid panel test and fasting plasma glucose test were needed to identify high-risk individuals, with costs derived from the Medicare Physician Fee Schedule 2014 (28).…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the entire population's awareness has an important role in most of the interventions. Primary prevention at the community level, as well as primary health care interventions, are usually the most cost-effective programs to prevent and reduce the burden of diabetes (38,39). There is a wide range of available resources and health care expenditure for individuals with diabetes in the region (7).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes health care needs and costs are likely to be dependent upon the duration of the condition and its severity and so are unlikely to differ greatly between the patient with newly diagnosed diabetes and someone with "prediabetes." The problem of treating "prediabetes" and diabetes as transition statesdseparate categories, each with its own disutility and costdalso applies to many of the modeling studies summarized in the CPSTF report (22), with the notable exception of those from the DPP. If someone is considered in a mathematical model as having developed diabetes and is thus assumed to share the average health disutility (23) and the annual costs (24) assessed for a population with diabetes, this may exaggerate the apparent benefits of prevention.…”
Section: "Preventing Diabetes"dthe Risks Of Extrapolationmentioning
confidence: 99%